2004
DOI: 10.1200/jco.2004.01.108
|View full text |Cite
|
Sign up to set email alerts
|

Cisplatin, Fluorouracil, and Leucovorin Induction Chemotherapy Followed by Concurrent Cisplatin Chemoradiotherapy for Organ Preservation and Cure in Patients With Advanced Head and Neck Cancer: Long-Term Follow-Up

Abstract: Induction chemotherapy with PFL followed by concurrent cisplatin chemoradiotherapy is well tolerated and results in a good likelihood of organ preservation and excellent PFS and OS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
47
0
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(52 citation statements)
references
References 32 publications
3
47
0
2
Order By: Relevance
“…We identified only one study in the literature using a treatment regimen similar to ours (Psyrri et al, 2004). Psyrri et al (2004) reported on a phase II study with 42 patients with stages III and IV head-and-neck cancer patients. At 2 years, the authors reported a local control rate of 76.3%, DSS of 69%, overall survival of 66.7% and rate of control of distant metastases of 79%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We identified only one study in the literature using a treatment regimen similar to ours (Psyrri et al, 2004). Psyrri et al (2004) reported on a phase II study with 42 patients with stages III and IV head-and-neck cancer patients. At 2 years, the authors reported a local control rate of 76.3%, DSS of 69%, overall survival of 66.7% and rate of control of distant metastases of 79%.…”
Section: Discussionmentioning
confidence: 99%
“…This rate is comparable to the other studies. In the phase II studies, using the sequential approach by Psyrri et al (Psyrri et al, 2004) and the SWOG study (Urba et al, 2005), the larynx preservation rates were 64.3 and 64%, respectively. Sequential treatment for advanced head-and-neck cancer SA Bhide et al…”
Section: Discussionmentioning
confidence: 99%
“…Presently, early-stage HNSCC tumors are treated with radiation or surgery (2) and in advanced cases, a multimodal approach is used often incorporating chemotherapy (3). Unfortunately, long-term survival remains relatively unchanged (4) and new therapeutic options are required to enhance overall survival (OS) of patients with HNSCC. Expression of the EGFR is associated with HNSCC pathogenesis and is upregulated in 90% of these tumors (5,6).…”
Section: Introductionmentioning
confidence: 99%
“…However, such treatment regimens are also frequently associated with significant short-term and long-term undesirable effects. [9][10][11][12] Novel approaches using cell-based immunotherapy have also been examined in human subjects with promising preliminary results. [13][14][15] Nevertheless, these modalities are still experimental.…”
mentioning
confidence: 99%